Wood products for home construction features of preparation - Utepbergenova, Лаура; Temirkhanov, Бағдат (Рroblems of engineering and professional education, 2023)
This article deals with traditional and modern methods of producing wood blanks for house building, as well as the advantages of new technologies. Based on the results of experiments conducted in Europe, the advantages of wood from other similar materials in construction are described.